Echocardiographic and Doppler flow observations in obstructed and nonobstructed hypertrophic cardiomyopathy - Gardin, Julius M.; Dabestani, Ali; Glasgow, Gordon A.; Butman, Samuel; Burn, Cora S.; Henry, Walter L. (The American journal of cardiology, 1985)
Some investigators have suggested that left ventricular (LV) ejection is completed much earlier than normal in patients with hypertrophic cardiomyopathy (HC), whether or not a LV outflow gradient is present, and they have therefore concluded that LV ejection is not impeded in HC, but merely ends early because of early completion of LV emptying. This possibility was examined using pulsed Doppler echocardiography to record ascending aortic flow velocity patterns in 20 patients with HC, 12 with evidence of LV outflow gradient at rest (obstructed HC) and 8 without evidence of a significant resting gradient (nonobstructed HC). Peak aortic flow velocity was similar in patients with nonobstructed HC (92 ± 26 cm/s) and those with obstructed HC (94 ± 26 cm/s) and in 20 normal subjects (92 ± 11 cm/s). However, mean ejection time measured from the aortic flow velocity tracing or aortic echogram was longer in those with obstructed HC (345 ± 30 ms) than in those with nonobstructed HC (296 ± 24 ms, p < 0.02) and in normal subjects (294 ± 19 ms, p < 0.01). Furthermore, a rapid decrease in aortic flow velocity in midsystole was seen in 11 of 12 patients with obstructed HC, but in none of the patients with nonobstructed HC or normal subjects. Doppler left atrial flow velocity recordings, obtained in 11 patients, demonstrated mitral regurgitation in 4 of 5 patients with obstructed HC but in none of 6 patients with nonobstructed HC. The temporal relation between the decrease in Doppler aortic flow velocity, the peaking of Doppler mitral regurgitant flow, and the onset of mitral valve-septal contact in midsystole—as well as observations regarding LV internal dimensional changes—suggest that the early deceleration of aortic blood flow in the patient with obstructed HC is not merely a result of early completion of mechanical systole by a hyperdynamic left ventricle. Rather, midsystolic aortic flow deceleration is at least in part a result of the anterior leaflet of the mitral valve impeding LV outflow and causing ejection of blood by an alternate route into the left atrium.